THE USE OF ENGLISH NOUN PHRASES - Lia Siska Selfi Perdani (Humaniora Scientia, 2014)
This study discusses English noun phrases. It focuses on the kinds of modifier and functions of noun phrase. This research is descriptive in nature. It was conducted through the following steps: collecting, classifying, and analyzing the data. The data were obtained from Time magazine of January 2013. The population of this research was all of the sentences containing noun phrases within the magazine. To get the sample, this research applied purposive sampling. So, the sample represents the information of the population of the data. Based on their categories, noun modifiers included nouns, adjectives, verbs, adverbs and function words. Due to their form, noun modifiers were words, phrases and clauses. In this case, words were the highest frequency in use, while noun clauses were the lowest. Functionally, noun phrases acted as subject, object, complement and modifier in sentence constructions. The most common function filled with noun phrase was subject, while, the least was modifier. Key Words : nominal phrase, head, modifier